BIM in construction management: automated quantity retrieval for progress claims - Chu, Yi Hao (Nanyang Technological University, 2022)
The emergence of Building Information Modelling (BIM) authoring software has given rise to the potential of effective and efficient information and data handling in the build industry. This project focuses on the issues of the traditional workflow of quantity retrieval for progress claim and proposed solution and alternate workflow to boost the efficiency by introducing automated quantity retrieval from BIM authoring software for progress claim. Software that were used in this project are Autodesk Revit, Revit Dynamo, Microsoft Excel, Python and C#.